Joubert syndrome 26 protein enforces compartmentalized motility of a ciliary kinesin - Shimin Wang; Ming Li; Guanghan Chen; Zhe Chen; Kexin Lei; Zeynep Ökten; Shanshan Xie; Tianhua Zhou; Wei Li; Guangshuo Ou (Proceedings of the National Academy of Sciences, 2025)
Cilia are essential cellular antennae that rely on precise motor-driven transport to assemble and function. Two kinesin-2 motors—kinesin-II and OSM-3 in Caenorhabditis elegans —cooperate to transport cargo along cilia, with kinesin-II operating in the middle segment and OSM-3 taking over distally. However, how kinesin-II is spatially confined to prevent its invasion into distal regions remains unclear. Here, we identify Joubert syndrome 26 protein (JBTS-26) as a critical regulator of this motor handover. JBTS-26 localizes to axonemal doublet microtubules in the ciliary middle segment, where it competes with kinesin-II for binding to the IFT-B subunit OSM-5/IFT88. This competition displaces kinesin-II from IFT particles, enabling OSM-3 to assume distal transport. Loss of JBTS-26 allows kinesin-II to invade the distal cilium and slows down IFT. Conversely, JBTS-26 overexpression accelerates IFT by prematurely releasing kinesin-II. Our findings reveal a mechanism for compartmentalized motor regulation and link defective motor handover to ciliopathy pathogenesis.